Relation between the physical demands and success in professional soccer players - Gomez-Piqueras, P.; Gonzalez-Villora, S.; Castellano, J.; Teoldo, I. (Journal of Human Sport & Exercise, 2019)
Background: The analysis of the efforts performed during a soccer match and its relation with the competitive success still presents numerous questions. Objective: 1) To describe and compare the physical demands (total covered meters and meters covered at high speed ranges), between the teams of the Spanish First and Second Division league. 2) To determine if the distance covered of the teams is related to the sports success (final classification, the points obtained and the goals in favour and against). Method: A total of 712 games (First and Second Division) were analysed using a computerized multi-camera system (Mediacoach, Mediapro and LaLiga ©). In order to quantify the physical performance, the following distances were recorded: total distance (TD), the distance covered between 21-24 km/h (DHI) and distance covered above 24km/h) (DVHI). In order to quantify the sports success, we considered the final classification, the obtained points as well as the goals in favour and against. Results: The total distance covered by the teams of the First and Second Division Leagues was similar, however, the distance covered at high intensity and distance covered at very high intensity was greater in the teams of the First Division (p<0.05; d of Cohen >1.2). No relations were detected between the meters covered and the recorded success indicators. Conclusion: This data should be taken into account by the coaches and physical trainers when guiding the training process of their teams. The distance covered during the competition does not have a direct relationship with success.